Insurance market as a tool for the development of the socio-economic sphere of Tajikistan - G. A. Yusupova (Управление)
Theoretical and methodological issues of assessing the insurance market of the Republic of Tajikistan in dynamics have been studied in the article, the “bottlenecks” of this market have been identified. The basic concepts of the insurance market have been substantiated and also the structure of the insurance market, indicators of insurance premiums and payments, level of payments, expenses of insurance organizations have been analysed, the main indicators of insurance market development have been assessed.One of the problems of assessing the activity of the insurance market in the Republic of Tajikistan is an insufficiently developed system for collecting and processing statistical information. At the same time, in 2015-2019, insurance premiums increased by 2.5 times, insurance payments by 1.05, but the level of payments decreased by 3.3 times. Unfortunately, the analysis of the composition and structure of expenses of insurance organizations reflects not stable, unstable, chaotic development of the country’s insurance market. The dynamics of deductions to insurance reserves, insurance premiums transferred to insurance, as well as the dynamics of insurance payments is spontaneous, as a result of existing problems in the development of insurance institutions. But, despite the growing trend in indicators of the level of development of the country’s insurance market, it is still far from the level of development in the countries of the near and far abroad. However, the potential of insurance will allow organizations of various types of property to become an internal long-term source of investment in the country’s economy.The problems of development of the insurance market of the Republic of Tajikistan have been revealed and conclusions and recommendations for its improvement have been formulated. The results of the study can be used in the process of developing a strategy for the development of the national economy and conducting social policy and state regulation of the economy taking into account the features and specifics of the insurance market of the country.